PENGEMBANGAN SIKAP SOSIAL SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK - Azwar, Beni; Santosa, Purba; Hutami, Nikku Panduning (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2023)
Abstract: This study aims to determine the development of students' social attitudes through group guidance services at SMAN 4 Rejang Lebong, where there are still students who show poor social attitudes, such as lack of empathy, indifferent, do not care even to the point of bullying their friends, so that efforts are needed to improve or the formation of good social attitudes through group guidance services, because group guidance services can train good social attitudes such as respecting the opinions of others, empathy and cooperation in helping to complement the opinions of others.This study used a descriptive approach, with data collection in the form of observations, interviews and data documentation, the research subject was the counseling teacher and 10 students of class XI IPS IV 10 students of SMA N 4 Rejang Lebong who were categorized as having problems with social attitudes and data analysis techniques, namely data reduction, data presentation, conclusion drawing, and data validation.The results of the study showed changes in students' social attitudes before the service and after group guidance. Students respect other people more, are patient and do not impose their will and are able to cooperate with others. group guidance services were held 2 times with the theme of how to appreciate and the importance of cooperation. In the activity stage the discussion develops by discussing respecting teachers, parents and friends, and being able to collaborate in class and live in society. At the end of the activity stage the supervising teacher provides motivation to students and students are committed to applying good social attitudes, respecting others and being able to cooperate wellKeywords: Group Guidance Services; Social Attitudes.Abstrak: Penelitian ini bertujuan untuk mengetahui pengembangan sikap Sikap sosial siswa melalui layanan bimbingan kelompok di Sekolah Menengah Atas Negeri 4 Rejang Lebong, yang masih ada siswa yang menunjukkan sikap sosial yang kurang baik, seperti kurang empati, cuek, tidak peduli bahkan sampai membully temannya, sehingga diperlukan upaya perbaikan atau pembentukan sikap sosial yang baik melalui layanan bimbingan kelompok, karena layanan bimbingan kelompok bisa melatih sikap sosial yang baik seperti menghargai pendapat orang lain, empati dan kerjasama dalam membantu melengkapi pendapat orang lain. Penelitian ini menggunakan pendekatan deskriptif, dengan pengumpulan data berupa observasi, wawancara dan dokumentasi data, subjek penelitian guru BK dan 10 orang siswa kelas XI IPS IV 10 siswa SMA N 4 Rejang Lebong yang dikategorikan beramasalah pada sikap sosial dan teknik analisis data yaitu reduksi data, penyajian data, penarikan kesimpulan, dan validasi data. Hasil penelitian adanya perubahan sikap sosial siswa sebelum layanan dan setelah bimbingan kelompok. Siswa lebih menghargai orang lain, sabar dan tidak memaksakan kehendak dan mampu Kerjasama dengan orang lain. layanan bimbingan kelompok dilaksanakan sebanyak 2 kali dengan tema cara menghargai dan pentingnya kerjasama. Dalam tahap kegiatan berkembang diskusi dengan membahas menghargai guru, orang tua serta teman-temannya, serta bisa kerjasama dalam kelas dan hidup bermasyarakat. Di akhir tahap kegiatan guru pembimbing memberikan motivasi pada siswa dan siswa berkomitmen akan menerapkan sikap sosial yang baik, menghargai orang lain serta dapat Kerjasama dengan baik.Kata Kunci: Layanan Bimbingan Kelompok; Sikap Sosial.